2021
DOI: 10.1007/s12155-021-10264-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Allocation and Root Characteristics of Early-Stage Poplars (Populus spp.) for Assessing Their Water-Deficit Response During SRC Establishment

Abstract: Early above- and belowground biomass fractionation, root diameter composition and allocation of cumulated fine root length per total leaf area of Populus clones have been measured for a pre-assessment of the risk for plantation establishment during spring drought conditions. Four clones of Populus × euramericana, and one P. nigra × P. maximowiczii clone (cv. Max 3), were planted in sandy mix substrate and were exposed to one normal and one deficit watering regime over 65-day greenhouse experiments conducted du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The results of this study add new novelty data with some of the published results from poplar plantations in Europe, in particular, in the vertical distribution of ne root biomass and production under different soil moisture scenarios. Some studies have reported that drought stress can lead to a decrease in root production and in poplar trees (Meyer et al, 2021;Regier et al, 2009). As young roots generally are physiologically more active, an increase in root turnover can increase the water use e ciency, but with an additional carbon cost (Eissenstat, Wells, Yanai, & Whitbeck, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study add new novelty data with some of the published results from poplar plantations in Europe, in particular, in the vertical distribution of ne root biomass and production under different soil moisture scenarios. Some studies have reported that drought stress can lead to a decrease in root production and in poplar trees (Meyer et al, 2021;Regier et al, 2009). As young roots generally are physiologically more active, an increase in root turnover can increase the water use e ciency, but with an additional carbon cost (Eissenstat, Wells, Yanai, & Whitbeck, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Both plantations were 5-year-old poplar stands established at a square spacing of 3.0 m x 2.0 m with the hybrid poplar (Populus x euramericana Dode (Guinier)). Clone 'AF16' was planted in Nivky, and clone 'AF18' in Gajary (Heilig et al 2021, Landgraf et al 2020, Meyer et al 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The test plantation was located in Pernek (48° 23' 55.04" N;17° 04' 43.97" E in WGS84), few kilometers northeast of the plant (48° 25' 01.81" N; 17° 02' 06.95"E). It was a 6-year-old poplar stand established at a square spacing of 3.0 m x 2.0 m with hybrid poplar (Populus x euramericana Dode (Guinier)), using the following mix of similar clones: AF13, AF 16 and AF18 (Landgraf et al 2020, Meyer et al 2021. The trees were planted on an ex-arable field, on flat and even terrain.…”
Section: Methodsmentioning
confidence: 99%